Mentoring For Professional Development In Universities In Rivers State, Nigeria - Obasi, Kenneth K.; Ohia, Adanma N. (Advances in Social Sciences Research Journal, 2018)
The study investigated the level of mentoring for professional development in the universities in Rivers State. The study adopted the descriptive survey design. Four research questions guided the study. The population of the study comprised all the three universities in Rivers State. All the lecturers in the three universities constituted the population of the respondents. The sample size of the respondents was 120 lecturers (30 HODs and 90 other lecturers). The instruments for the study were questionnaire and structured interview. The questionnaire was validated and tested for reliability with Crombach Alpha with reliability indices of 0.86, 0.84, 0.88 and 0.89 respectively. Mean and Standard Deviation were used to answer the research questions. The study revealed that the only official policy on mentoring was the directive of the National Universities Commission on the use of the recommended staff – mix – ratio for mentoring. In the three universities, there is no formalized platform or framework for mentoring for staff development, except in some cases where research assistants are assigned to professors to guide them and supervise their thesis. There is little or no institutional provision for mentoring. It was therefore recommended that the NUC and the individual universities should come up with more realistic and effective polices on mentoring. Each department should have a mentoring committee or coordinator for effective packaging and implementation of mentoring.